Development of vapor deposited silica sol–gel particles for use as a bioactive materials system1. Issue 6 (27th November 2012) - Snyder, Katherine L.; Holmes, Hallie R.; VanWagner, Michael J.; Hartman, Natalie J.; Rajachar, Rupak M.
Abstract: Silica‐based sol–gel and bioglass materials are used in a variety of biomedical applications including the surface modification of orthopedic implants and tissue engineering scaffolds. In this work, a simple system for vapor depositing silica sol–gel nano‐ and micro‐particles onto substrates using nebulizer technology has been developed and characterized. Particle morphology, size distribution, and degradation can easily be controlled through key formulation and manufacturing parameters including water:alkoxide molar ratio, pH, deposition time, and substrate character. These particles can be used as a means to rapidly modify substrate surface properties, including surface hydrophobicity (contact angle changes >15°) and roughness (RMS roughness changes of up to 300 nm), creating unique surface topography. Ions (calcium and phosphate) were successfully incorporated into particles, and induced apatitie‐like mineral formation upon exposure to simulated body fluid Preosteoblasts (MC3T3) cultured with these particles showed up to twice the adhesivity within 48 h when compared to controls, potentially indicating an increase in cell proliferation, with the effect likely due to both the modified substrate properties as well as the release of silica ions. This novel method has the potential to be used with implants and tissue engineering materials to influence cell behavior including attachment, proliferation, and differentiation via cell–material interactions to promote osteogenesis. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.